Evaluation of translucency of monolithic zirconia and framework zirconia materials - Tuncel, İlkin (J Adv Prosthodont, 2016)
PURPOSE: The opacity of zirconia is an esthetic disadvantage that hinders achieving natural and shade-matched restorations. The aim of this study was to evaluate the translucency of non-colored and colored framework zirconia and monolithic zirconia. MATERIALS AND METHODS: The three groups tested were: non-colored framework zirconia, colored framework zirconia with the A3 shade according to Vita Classic Scale, and monolithic zirconia (n=5). The specimens were fabricated in the dimensions of 15×12×0.5 mm. A spectrophotometer was used to measure the contrast ratio, which is indicative of translucency. Three measurements were made to obtain the contrast ratios of the materials over a white background (L(*)w) and a black background (L(*)b). The data were analyzed using the one-way analysis of variance and Tukey HSD tests. One specimen from each group was chosen for scanning electron microscope analysis. The determined areas of the SEM images were divided by the number of grains in order to calculate the mean grain size. RESULTS: Statistically significant differences were observed among all groups (P<.05). Non-colored zirconia had the highest translucency with a contrast ratio of 0.75, while monolithic zirconia had the lowest translucency with a contrast ratio of 0.8. The mean grain sizes of the non-colored, colored, and monolithic zirconia were 233, 256, and 361 nm, respectively. CONCLUSION: The translucency of the zirconia was affected by the coloring procedure and the grain size. Although monolithic zirconia may not be the best esthetic material for the anterior region, it may serve as an alternative in the posterior region for the bilayered zirconia restorations.